ANTECEDENTS OF REVISIT INTENTION WITH MEDIATED CUSTOMER SATISFACTION A STUDY ON MILLENNIAL CONSUMER BEHAVIOUR AT THEME RESTAURANT IN JAKARTA - Yuliantoro, Nonot; Juliana, Juliana; Laurenzia, Sharleen; Tanzil, Sheily Triratnasari (LPPM Institut Pendidikan Nusantara Global, 2023)
The main aim of this research was to investigate the potential impact of food quality, dinerserve, and dinescape on customers' likelihood to revisit theme restaurants in Jakarta. Additionally, the study sought to explore whether customer satisfaction played a mediating role in this relationship. To achieve these objectives, a survey method was employed, and data collection was carried out using an online questionnaire instrument. The target population of the study consisted of millennial consumers aged 18 to 40 years living in Jakarta, Bogor, Depok, Tangerang, and Bekasi. The data collection took place in October 2021. A purposive sampling technique was utilized to select 200 valid respondents, who were then subjected to data analysis using the PLS SEM (Partial Least Squares Structural Equation Modeling) program with smartpls 3.29 software. The findings from this research indicate that food quality, dinerserve, and dinescape significantly and positively influence customer satisfaction. Furthermore, it was observed that customer satisfaction itself plays a significant and positive role in determining the effect on revisit intention at theme restaurants in Jakarta.